2015
DOI: 10.1016/j.yhbeh.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of brain somatostatin receptor 2 in the regulation of feeding and drinking behavior

Abstract: Somatostatin was discovered four decades ago as hypothalamic factor inhibiting growth hormone release. Subsequently, somatostatin was found to be widely distributed throughout the brain and to exert pleiotropic actions via interaction with five somatostatin receptors (sst1-5) that are also widely expressed throughout the brain. Interestingly, in contrast to the predominantly inhibitory actions of peripheral somatostatin, the activation of brain sst2 signaling by intracerebroventricular injection of stable soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 111 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…In the ARH, a large proportion of SST-expressing cells coexpressed GLP-1R. SST is associated with the inhibition of growth hormone (73) and a range of extrapituitary effects, including body temperature and visceral functions (74)(75)(76)(77). When delivered centrally, SST increases food intake (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…In the ARH, a large proportion of SST-expressing cells coexpressed GLP-1R. SST is associated with the inhibition of growth hormone (73) and a range of extrapituitary effects, including body temperature and visceral functions (74)(75)(76)(77). When delivered centrally, SST increases food intake (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin is a multifunctional neuropeptide produced by the periventricular nucleus of the hypothalamus, the ARC, and other neuronal populations (Guillemin and Gerich, 1976). It binds to receptors located in various brain nuclei involved in feeding regulation, notably the ARC, and it regulates food intake in various mammalian species (Lotter et al, 1981;Danguir, 1988;Fehlmann et al, 2000;Stengel et al, 2010Stengel et al, , 2015. Interestingly, independent studies have reported that Kp (Revel et al, 2006a;Smith et al, 2008), RFRP-3 (Revel et al, 2008;Smith et al, 2008), NPY (Lakhdar-Ghazal et al, 1995Reuss and Olcese, 1995;Skinner and Herbison, 1997), b-endorphin (Roberts et al, 1985;Ebling and Lincoln, 1987), and somatostatin (Webb et al, 1985;Herwig et al, 2012;Klosen et al, 2013;Dumbell et al, 2015) display significant variations in the brain of different mammalian species placed in artificial long or short photoperiods.…”
mentioning
confidence: 99%
“…The role of SST in the regulation of food intake and energy store and expenditure is most controversial. Previous studies support the pro-and anti-satiety effect of SST that depends on species, doses, and mode of administration [26,163,168]. It is not well understood if SST regulates satiety via direct or indirect mechanisms.…”
Section: Role Of Somatostatin and Its Receptors In Satietymentioning
confidence: 98%
“…A summary of the physiological actions of SST and associated receptor subtypes in target sites is shown in Figure 2. In addition to the anti-proliferative effect in peripheral tissue, SST exerts a significant role in food intake and drinking behaviour via activation of specific receptors [26,121,122,[163][164][165]. Besides the prominent role in the regulation of hormonal secretion, SSTR subtypes play a critical role in modulation of complex downstream signal transduction pathways [2,3].…”
Section: Somatostatin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation